Hollow morphology, crystallization and phase transformation behavior of magnetic hollow composite materials based lignocellulose fibers via heat treatment. (August 2020) - Pan, Yanfei; Zhang, Chenxia; Yu, Haibiao; Wu, Yuhang; Yin, Dingwen; Zhao, Dongliang; Yu, Xiaofang; Hao, Yinan; Zhao, Shengli; Huang, Jintian
Abstract: The hollow composite materials with unique topological structure and ideal appearance morphology were conducted via high-heat process to investigate the relationship of magnetic hollow materials between structure and performance. The hollow composite materials were characterized via scanning electron microscope (SEM), Thermo-gravimetric analyses (TGA), X-ray diffraction (XRD), vibration sample magnetic flowmeter (VSM) and X-ray photoelectron spectroscopy (XPS). The results revealed that there were no distinct effect on both the size of hollow cavity and the property of hollow structure via heat treatment. The weight loss occurred between 290 °C and 450 °C, indicating that lignocellulose fibers (LCFs) of metallization lignocellulose fibers (MLCFs) was 4.54%, 5.60%, respectively. The characteristic diffraction peaks corresponding to Ni3 P had appeared. In addition, there was the crystallite size between 4.7 nm and 26.8 nm for Ni deposited on LCFs by the measurement of XRD, further indicating that particle size could be fined via high-heat treatment. The crystalline properties of the hollow composite materials via high-heat treatment at 400 °C were optimum. The mechanism of high-temperature heat treatment for Ni crystal grains growth was analyzed. Here, the magnetic parameters of saturation magnetization (Ms), coercive (HC ) and remanence (Mr) were good. The coatings surface can absorb some Ni 2+ ions and oxygen and the metal Ni can be oxidized NiO via heat treatment. Highlights: Local inner cavity had a small shape change via heat treatment. The weight loss ratio was 4.54%, 5.60%, respectively. The crystallite size of hollow coatings was from 47 to 268 Å with increasing in high-heat treatment. The heat treatment was obvious with saturation magnetization, remanence and coercive of hollow coatings. The coatings surface can absorb some Ni 2+ ions and oxygen.